Macrophage activation in acute exacerbation of idiopathic pulmonary fibrosis. - Jonas Christian Schupp; Harald Binder; Benedikt Jäger; Giuseppe Cillis; Gernot Zissel; Joachim Müller-Quernheim; Antje Prasse (PLoS ONE, 2015)
BACKGROUND:Acute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) is a common cause of disease acceleration in IPF and has a major impact on mortality. The role of macrophage activation in AE of IPF has never been addressed before. METHODS:We evaluated BAL cell cytokine profiles and BAL differential cell counts in 71 IPF patients w/wo AE and in 20 healthy volunteers. Twelve patients suffered from AE at initial diagnosis while sixteen patients developed AE in the 24 months of follow-up. The levels of IL-1ra, CCL2, CCL17, CCL18, CCL22, TNF-α, IL-1β, CXCL1 and IL-8 spontaneously produced by BAL-cells were analysed by ELISA. RESULTS:In patients with AE, the percentage of BAL neutrophils was significantly increased compared to stable patients. We found an increase in the production rate of the pro-inflammatory cytokines CXCL1 and IL-8 combined with an increase in all tested M2 cytokines by BAL-cells. An increase in CCL18 levels and neutrophil counts during AE was observed in BAL cells from patients from whom serial lavages were obtained. Furthermore, high baseline levels of CCL18 production by BAL cells were significantly predictive for the development of future AE. CONCLUSIONS:BAL cell cytokine production levels at acute exacerbation show up-regulation of pro-inflammatory as well as anti-inflammatory/ M2 cytokines. Our data suggest that AE in IPF is not an incidental event but rather driven by cellular mechanisms including M2 macrophage activation.